Acute Pannexin 1 Blockade Mitigates Early Synaptic Plasticity Defects in a Mouse Model of Alzheimer’s Disease - Flores-Muñoz, Carolina; Gómez, Bárbara; Mery, Elena; Mujica, Paula; Gajardo, Ivana; Córdova, Claudio; Lopez-Espíndola, Daniela; Durán-Aniotz, Claudia; Hetz, Claudio; Muñoz, Pablo; Gonzalez-Jamett, Arlek M.; Ardiles, Álvaro O. (Frontiers in Cellular Neuroscience, 2020)
Synaptic loss induced by soluble oligomeric forms of the amyloid β peptide (sAβos) is one of the earliest events in Alzheimer´s disease (AD) and is thought to be the major cause of the cognitive deficits. These abnormalities rely on defects in synaptic plasticity, a series of events manifested as activity-dependent modifications in synaptic structure and function. It has been reported that Pannexin1 (Panx1), a non-selective channel implicated in cell communication and intracellular signaling, modulates the induction of excitatory synaptic plasticity under physiological contexts and contribute to neuronal death under inflammatory conditions. Here, we decided to study the involvement of Panx1 in functional and structural defects observed in excitatory synapses of the APP/PS1 transgenic (Tg) mice, an animal model of AD. We found an age-dependent increase in the Panx1 expression that correlates with increased Aβ levels in hippocampal tissue from Tg mice. Congruently, we also observed an exacerbated Panx1 activity upon basal conditions and in response to glutamate receptor activation. The acute inhibition of Panx1 activity with the drug probenecid (PBN) did not change neurodegenerative parameters such as amyloid deposition or astrogliosis but it significantly reduced excitatory synaptic defects in the AD model, by normalizing long term potentiation and depression, and improving dendritic arborization and spine density in hippocampal neurons of the Tg mice. These results suggest a major contribution of Panx1 in the early mechanisms leading to the synaptopathy in AD. Indeed, PBN induced a reduction in the activation of p38MAPK, a kinase widely implicated in the early neurotoxic signaling in AD. Our data strongly suggest that an enhanced expression and activation of Panx1 channels contribute to the Aβ-induced cascades leading to synaptic dysfunction in AD.